Isolation, Characterisation And Pathogenicity Of Mycoplasma Gallinarum In Village Chicken - Abdul Majid, Mohd Shah (1995)

(untitled)
This study was conducted to determine the presence of mycoplasma infections in village chickens in Malaysia. This study comprised the isolation and characterisation of Mycoplasma gallinarum and its pathogenicity in village chickens. The occurrence of M. gallinarum in fresh eggs, infertile and/or early dead germs, dead-in-shell and/or pipped embryos was investigated. For mycoplasma isolation , samples were taken from the vitelline membrane, yolk, and yolk sac. M. gallinarum was not present in all the eggs and embryos sampled. Day-old-village chicken chicks and adult village chickens were swabbed at the choanal cleft region , an alternative site for mycoplasma isolation. M. gallinarum was not present in the day-old-chicks. However, of the 550 adult birds sampled , 294 were carriers of mycoplasma. The isolation rate varied from 26 . 3 to 73 per cent. The mycoplasma species isolated from village chicken was identified as M. gallinarum based on biochemical and serological tests. The indirect immunoperoxidase test was easy to perform and results easy to read. The morphological studies of the M. gallinarum isolates were studied by scanning electron and transmission electron microscopy and the result showed that morphologically M. gallinarum from village chicken was similar to that of earlier reports. M. gallinarum remains viable in drinking water for up to a 48 hr period when the inoculum size is 108 colony forming units but not at 102 colony forming units. The effect of M. gallinarum isolated from village chicken on embryonated village chicken eggs was investigated. Seven-, ten-, twelve- and eighteen-day-old embryos were inoculated with medium containing 106 colony forming units of M. gallinarum or uninfected medium and incubated at 37°C until hatched. No significant difference was observed between the infected embryos which failed to hatch and those which hatched or between them and the group inoculated with medium only. A much higher percentage of the eggs inoculated as 18-day-old embryos hatched than those inoculated at seven, ten and twelve days intervals. In another pathogenicity study, mixed infection with M. gallinarum and Newcastle disease virus was examined. Day-old village chicken chicks were vaccinated intranasally with F strain of Newcastle disease virus and inoculated intratracheally with M. gallinarum simultaneously and changes on the tracheal epithelium were observed by scanning electron microscopy. At day 3 postvaccination/ infection, major alterations of the epithelial surface were visible and the epithelial surface were apparently normal by day 7. This study has successfully achieved its objectives by isolating , characterising and conducting pathogenicity studies of M. gallinarum in village chicken . Pathogenicity studies show that M. gallinarum is mildly virulent and the overall impact of M. gallinarum infection in village chickens needs further investigation .